Implementasi Clinical Risk Management pada Instalasi Gawat Darurat di RSUD Banyumas - Intiasari, Arih Diyaning; cahyawaning, putri titis; Aji, Budi (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2018)
Background: Patient safety is a system in hospital to make patient care safer. The system includes risk assessment, identification and management of patient risk, incident analysis and report, capability of learning from an incident and its follow-up, and solution implementation to minimize risk. Risk management is reducing mistakes and accidents as low as possible, and minimizing possible worst outcome for patient. Methodology: This research is an evaluative descriptive qualitative research. Informants in this research are 4 health workers, 2 stakeholders, and 2 Hospital committee chosen using purposive sampling method. The techniques used for data collection are in-depth interview, observation, and documentation. Data analysis used is content analysis. Result: Four global themes obtained are: input implementation is still not good; implementation process is good enough but there are some obstacles; output implementation has some drawback; implementation of programs has some obstacles; role of policy makers for strategy in implementation. Conclusion: CRM implementation in Emergency Room of RSUD Banyumas is passable and could provide some benefits to its human resources, however some drawbacks still exist in the implementation.